기능성 소화불량증 환자의 심리적 요소에 관한 연구 - 이규택; Kyu Taek Lee; 이풍렬; Poong Lyul Rhee; 김재준; Jae Jun Kim; 고광철; Kwang Cheol Koh; 백승운; Seung Woon Paik; 이종철; Jong Chul Rhee; et al. (The Korean journal of medicine, 1996)
Objectives: The role of psychological factors contributing to the etiology of functional dyspepsia has been consistently recognized in the U.S. and the European countries. However, no study has been done with Korean patients. The purpose of the present study was to identify the specific psychological factors involved in functional dyspepsia in Korean population and compare them with those of Western counterpart. Further, it purported to examine how these factors differed in two patient groups of functional dyspepsia: a group of patients with delayed gastric emptying time and a group of patients with normal gastric emptying time. Methods: A double-blind study was done with 70 subjects; The internists and the psychologists were not aware of the status of the gastric emptying time of a patient when they measured the gastric emptying time and administered the MMPI, respectively. The patients (n=50) were suffering from dyspepsia for more than three months and complained of moderate to severe dysmotility symptoms. They were all outpatients in a private hospital. Normal controls were recruited via personal contact. Results: The psychological factors that significantly differentiated the patients from the normal controls were Depression (Scale 2), Hypochondriasis (Scale 1), Hysteria (Scale 3), and Psychasthenia (Scale 7). These factors were similar to those found to be significant in Western functional dyspeptic population. There was no association between the psychological profiles and the presence of delayed gastric emptying time. Two patient groups scored very similarly on all ten clinical scales. Among the 50 patients tested 12 patients received the clinical diagnoses and were recommended for psychiatric referral. The recommendations were based on a psychological interview and results of the MMPI of each patient which were administered by psychologists. Conclusion: The results of the study support the psychological factors in functional dyspepsia. However, it is difficult to conclude whether these factors are etiological in nature.